Exercise and fractures in postmenopausal women. Final results of the controlled Erlangen Fitness and Osteoporosis Prevention Study (EFOPS) - Kemmler, Wolfgang; Bebenek, Michael; Kohl, Matthias; von Stengel, Simon (Osteoporosis international, 2015)
The EFOPS trial clearly established the positive effect of long-term exercise on clinical low-trauma fractures in postmenopausal women at risk. Bearing in mind that the complex anti-fracture exercise protocols also affect a large variety of diseases of increased age, we strongly encourage older adults to perform multipurpose exercise programs.Physical exercise may be an efficient option for autonomous fracture prevention during increasing age. The aim of the study was to evaluate the effect of exercise on clinical overall fracture incidence and bone mineral density (BMD) in elderly subjects at risk.In 1998 initially, 137 early-postmenopausal, osteopenic women living in Erlangen-Nuremberg, Germany, were included in the EFOPS trial. Subjects of the exercise group (EG; n = 86) conducted two supervised group and two home exercise sessions/week while the control group (CG; n = 51) was requested to maintain their physical activity. Primary study endpoints were clinical overall low-trauma fractures determined by questionnaires, structured interviews, and BMD at the lumbar spine and femoral neck assessed by dual-energy X-ray absorptiometry.In 2014, 105 subjects (EG: n = 59 vs. CG: n = 46) representing 1680 participant-years were included in the 16-year follow-up analysis. Risk ratio in the EG for overall low-trauma fractures was 0.51 (95% confidence interval (95% CI) 0.23 to 0.97, p = .046), rate ratio was 0.42 (95% CI 0.20 to 0.86, p = .018). Based on comparable baseline values, lumbar spine (MV -1.5%, 95% CI -0.1 to -2.8 vs. -5.8%, -3.3 to -7.2%) and femoral neck (-6.5%, -5.2 to -7.7 vs. -9.6%, -8.2 to 11.1%) BMD decreased in both groups; however, the reduction was more pronounced in the CG (p <= .001).This study clearly evidenced the high anti-fracture efficiency of multipurpose exercise programs. Considering furthermore the favorable effect of exercise on most other risk factors of increasing age, we strongly encourage older adults to perform multipurpose exercise programs.
EVALuna2:10110